The role of cognitive metaphor in the formation and presentation of Imam Ali’s Ideological System in Nahj al-Balagha: The analysis of the conceptual metaphors: THE WORLD IS AN INFERIOR, DETESTABLE OBJECT as examples - Zare, Afarin (Al-Adab Journal, 2023)
Cognitive metaphor, known as a set of mappings from the source domain to the target one, is to a large extent the basis of our understanding of the world; Therefore, it always occurs in our daily life and is used in various issues such as society, politics, law, philosophy, psychology, mathematics, etc. Considering the high capacity that this type of metaphor has in generating ideas, hypotheses, and theories, as well as persuading the audience and shaping behavior, it has been used as an efficient tool in Islamic holy texts; because these texts have conceptualized divine teachings and abstract concepts creatively and uniquely humans the correct way of life; understanding, analyzing and also transferring these teachings and concepts is possible with the help of conceptual metaphor. According to what has been said, it is necessary to use the cognitive approach in analyzing the discourse of Islamic holy texts; For this reason, the present study uses cognitive metaphor to analyze the metaphor: "THE WORLD IS AN INFERIOR ODIOUS OBJECT" in order specify the nature of the mentioned metaphor and explain how we understand it, and the role of this metaphor in creating transformation in human thought and behavior. The most important achievement of this research is that if the various conceptual metaphors in the world domain, which are the product of the scholarly and artistic conceptualization of Imam Ali (PBUH), enter the conceptual system of humans, it can change their vision and consequently their perceptions and actions, and in fact, lead to a fundamental cultural revolution.